Positive adult experiences as turning points for better adult mental health after childhood adversity - Crandall, AliceAnn; Magnusson, Brianna M.; Barlow, Melissa J.; Randall, Hannah; Policky, Abigail L.; Hanson, Carl L. (Frontiers in Public Health, 2023)
Background The purpose of this study was to examine whether positive adult experiences (PAEs) were associated with lower odds for anxiety and depression even in the presence of high adverse childhood experiences (ACEs) or low positive childhood experiences (PCEs). Methods The sample was comprised of 435 adults (48% female), ages 18–56 years and who were living in the United States. Participants completed a survey about their childhood experiences, PAEs, and mental health. A series of multiple logistic regression models were estimated in Stata 17 to examine the aims. Results Positive childhood experiences were associated with higher PAE scores, but ACEs did not significantly correlate with PAEs. Positive adult experiences were associated with lower odds of moderate-to-severe anxiety and depression, especially among those who had experienced high ACEs or low PCEs. Younger adults were more likely to experience a positive benefit from PAEs compared to adults 35 years and older. Conclusion Even when ACEs were high or PCEs were low, adults with high PAEs had lower odds for moderate-to-severe anxiety and/depression. Positive adult experiences may be an opportunity to turn the tide for individuals who experienced childhood adversity and/or low levels of support or connection.